2018
DOI: 10.1038/s41598-018-25295-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Autophagy by a microRNA-mediated Signaling Cascade in Diabetes-induced Renal Glomerular Hypertrophy

Abstract: Autophagy plays a key role in the pathogenesis of kidney diseases, however its role in diabetic nephropathy (DN), and particularly in kidney glomerular mesangial cells (MCs) is not very clear. Transforming Growth Factor- β1 (TGF-β), a key player in the pathogenesis of DN, regulates expression of various microRNAs (miRNAs), some of which are known to regulate the expression of autophagy genes. Here we demonstrate that miR-192, induced by TGF-β signaling, plays an important role in regulating autophagy in DN. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…miR-NA-181a downregulates DEPTOR (mTOR inhibitor) and activates mTORC2, which activates Akt in TGFβ-induced glomerular MC hypertrophy and ECM protein expression [ 91 ]. Autophagy inhibition by the miR-192 cascade induces hypertrophy through Akt activation and FoxO3a phosphorylation [ 92 ]. About 40 miRNAs are included in the miR-379 cluster, which is regulated by endoplasmic reticulum (ER) stress in DKD [ 19 ].…”
Section: Ncrnas In the Early Stage Of Dkdmentioning
confidence: 99%
“…miR-NA-181a downregulates DEPTOR (mTOR inhibitor) and activates mTORC2, which activates Akt in TGFβ-induced glomerular MC hypertrophy and ECM protein expression [ 91 ]. Autophagy inhibition by the miR-192 cascade induces hypertrophy through Akt activation and FoxO3a phosphorylation [ 92 ]. About 40 miRNAs are included in the miR-379 cluster, which is regulated by endoplasmic reticulum (ER) stress in DKD [ 19 ].…”
Section: Ncrnas In the Early Stage Of Dkdmentioning
confidence: 99%
“…One severe complication of T2DM is type 2 diabetic nephropathy (T2DN), which is characterized by hypertension, albuminuria, and a progressive decline in glomerular filtration rate, developing into end-stage renal disease [ 17 , 18 ]. There is increasing evidence showing that TGF-β1 takes part in the pathogenesis of T2DN [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA‐22 is found to suppress autophagy and inhibition of the endogenous miRNA‐22 increased autophagy and alleviated high glucose‐induced Col 4 and α‐SMA expression in NRK‐52E cells . Deshpande et al reported that the expression of autophagy genes was decreased in kidneys of STZ‐induced and db/db diabetic mice. miRNA‐192 inhibitors can reverse the reduction of autophagy genes in these mice.…”
Section: The Role Of Mirnas In the Pathogenesis Of Dkdmentioning
confidence: 99%
“…In kidneys of diabetic miRNA‐192‐KO mice, downregulation of autophagy genes was also attenuated. In mouse glomerular MCs with TGF‐β1 stimulation, miRNA‐192 mimic oligonucleotides decreased the expression of autophagy genes, indicating miRNA‐192 as a potential therapeutic target for DKD …”
Section: The Role Of Mirnas In the Pathogenesis Of Dkdmentioning
confidence: 99%